Badger Ballistics Midwest High Powered Rocket Launch Proceedings Report - Conway, Sam (Proceedings of the Wisconsin Space Conference, 2023)
In this competition, UW-Madison AIAA was tasked with building one team rocket and seven accompanying rockets to be launched, each with unique design aspects. To design the rockets, OpenRocket simulations were used as well as SolidWorks. The rockets differed in a multitude of ways including number of fins and parachutes, motor size, and material. The fin numbers ranged from three to six fins and the team rocket featured dual deploy parachutes versus single deployment in the other seven rockets. The rockets featured two motor brands Cesaroni and Aerotech, with H, I & J level motors. Additionally, there were five rockets made from cardboard, two from fiberglass, and one made of polystyrene. These different design aspects were input into OpenRocket to simulate the expected performance of each rocket. On launch day each rocket was equipped with altimeters that were able to collect the flight data, which was then compared to the simulation to analyze how well the rockets performed compared to their expected performance. Based on the diversity of rockets and the execution of the team on launch day, the team finished second overall in the competition.